Profile of Students’ Difficulties to Learn Geometry of Mathematics Education Study Program - Abdurrahman Abdurrahman; Nofriyandi Nofriyandi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study describes mathematics education students' learning difficulties of Mathematics Education Study Program students at Riau Islamic university in Riau Province. This research is mixed-method research. The population in this study were students of Mathematics education at the Islamic University of Riau. The sampling technique uses a purposive approach by taking all active students and have studied geometry. The data collection instrument in this study used a questionnaire and interview guidelines. Data analysis used quantitative descriptive and qualitative descriptive. The analysis results show that 55.7% have difficulty remembering the concepts that have been studied (postulates, theorems, definitions, principles, procedures/operations, facts). 41% of students have difficulty understanding any geometry lecture material. 38.5% of students cannot understand the intent or problem in the given geometry problem. 54.9% of students cannot apply postulates/theorems/solve geometry problems. 41.8% of students cannot determine and sequence the steps in solving geometry problems. 36.9% of students cannot carry out a sequential, correct, and complete calculation process in solving geometry problems. There are 41% of students of the Mathematics Education Study Program at the Islamic University of Riau who are less able to be thorough and careful in solving geometry problems